Предмет: Алгебра, автор: vladasilivanova11

8 пожалуйста срочно ​

Приложения:

Ответы

Автор ответа: MagdaSinger
0

Ответ:

\dfrac{ 7  }{ 5-2 \sqrt{ 6 }    }   =  \dfrac{ 7(5+2 \sqrt{ 6  }  )  }{ (5-2 \sqrt{ 6)  }  (5+2 \sqrt{ 6}  )  }   =  \dfrac{ 7(5+2 \sqrt{ 6}  )  }{ (5  ^ { 2  }  -(-2 \sqrt{ 6 }  )  ^ { 2  }    }   =  \dfrac{ 7(5+2 \sqrt{ 6 }  )  }{ 25-24  }   = \\=7(5+2 \sqrt{ 6  }  ) = 35+14 \sqrt{ 6  }

Объяснение:

Похожие вопросы
Предмет: Английский язык, автор: kykimertyn
Предмет: Математика, автор: пух8564